2021
DOI: 10.1002/qj.4150
|View full text |Cite
|
Sign up to set email alerts
|

Characterising extratropical near‐tropopause analysis humidity biases and their radiative effects on temperature forecasts

Abstract: A cold bias in the extratropical lowermost stratosphere in forecasts is one of the most prominent systematic temperature errors in numerical weather prediction models. Hypothesized causes of this bias include radiative effects from a collocated moist bias in model analyses. Such biases would be expected to affect extratropical dynamics and result in the misrepresentation of wave propagation at tropopause level. Here the extent to which these humidity and temperature biases are connected is quantified. Observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 52 publications
8
15
0
Order By: Relevance
“…The cold biases in wintertime polar cap temperatures (corresponding to stronger polar stratospheric winds), and cold biases in the extratropical upper troposphere/lower stratosphere are longstanding biases that are similar to what has been documented in other weather and climate models (Charlton-Perez et al, 2013;Bland et al, 2021). The stratospheric polar cap temperature biases generally point to a dynamical cause related to parameterized gravity wave drag, given that wave-mean flow interactions and the ensuing residual circulations are responsible for driving local zonal mean temperatures away from radiative equilibrium.…”
Section: Severalsupporting
confidence: 56%
See 1 more Smart Citation
“…The cold biases in wintertime polar cap temperatures (corresponding to stronger polar stratospheric winds), and cold biases in the extratropical upper troposphere/lower stratosphere are longstanding biases that are similar to what has been documented in other weather and climate models (Charlton-Perez et al, 2013;Bland et al, 2021). The stratospheric polar cap temperature biases generally point to a dynamical cause related to parameterized gravity wave drag, given that wave-mean flow interactions and the ensuing residual circulations are responsible for driving local zonal mean temperatures away from radiative equilibrium.…”
Section: Severalsupporting
confidence: 56%
“…The cold extratropical UTLS biases, on the other hand, are likely to be radiatively driven, related to excessive leakage of water vapor into the lower stratosphere (e.g., Bland et al, 2021). Both of these issues are dependent upon vertical resolution, which likely explains why the biases in the low-top systems (which have fewer levels in the stratosphere and coarser resolution in the UTLS) are generally more severe than those in the high-top systems.…”
Section: Severalmentioning
confidence: 99%
“…ERA-5 forecasts are produced twice daily (00, 12 UTC) using ECMWF's Integrated Forecasting System (IFS). For the statistics of the lapse rate hourly ERA-5 reanalysis data were retrieved from the Copernicus Data Service (Copernicus Climate Change Service (C3S), Temperature data from ERA-5 agree well with MOZAIC in-situ data and a recent comparison with radiosonde data (Bland et al, 2021) confirms the good quality of the reanalysis' temperature in the upper troposphere and lower stratosphere.…”
Section: Reanalysis Datamentioning
confidence: 64%
“…Above the ExTL, the concentration of water vapor approaches a low and vertically constant background value (e.g., Hintsa et al, 1994) which is determined by the stratospheric transport from tropics (Fueglistaler et al, 2009) within the Brewer-Dobson-Circulation (e.g., Dobson et al, 1946;Brewer, 1949) on time scales from months to years. The complexity of transport and mixing processes is mirrored in the high variability of water vapor in the extratropical UTLS on synoptic and seasonal time scales (e.g., Pan et al, 2000;Randel and Wu, 2010;Zahn et al, 2014;Dyroff et al, 2015;Bland et al, 2021;Schäfler et al, 2022, in prep. ).…”
Section: Introductionmentioning
confidence: 99%
“…Current operational analyses and forecasts are known to possess a distinct moist bias in the extratropical LS which is causing a co-located cold bias (Stenke et al, 2008;Diamantakis and Flemming, 2014;Shepherd et al, 2018). Recently, Bland et al (2021) used radiosonde observations of a two-month period in fall and confirmed the earlier documented moist bias (about 70 % in the LS) in current operational analyses and forecasts of the European Centre for Medium-Range Weather Forecast's (ECMWF) Integrated Forecast System (IFS) and the Met Office's Unified Model (METUM) and a co-located cold bias. For a comprehensive overview of the studies https://doi.org/10.5194/acp-2022-505 Preprint.…”
Section: Introductionmentioning
confidence: 99%